Exploring Volunteering and Its Perceived Influence on Students’ Social Responsibility In Azerbaijani Higher Education - Ganbarli, Dinara (ADA University, 2025)
This study aimed to explore the perceived influence of volunteering on the development of students’ social responsibility within Azerbaijani higher education. The literature review examined relevant global and local research, along with theoretical frameworks such as Vygotsky’s Sociocultural Theory and Bandura’s Social Learning Theory, to better understand how volunteerism may shape students’ moral, cognitive, and social development. The study applied a qualitative descriptive research design, data were collected through semistructured interviews with 12 participants, including both current students and alumni actively engaged in volunteering. A thematic analysis of the data identified several key findings. The study findings revealed how volunteering is perceived to contribute to the development of social responsibility among students, along with the benefits and challenges they faced during the process. The findings emphasize the need for more structured volunteer programs to maximize the transformative benefits of volunteering. Future large-scale research is recommended to deepen understanding and contribute to the more effective integration of volunteering into higher education practices in Azerbaijan.
Keywords: Voluntarism -- Social aspects.; Student volunteers -- Attitudes.; Social responsibility -- Study and teaching (Higher).; Higher education -- Moral and ethical aspects.; Universities and colleges -- Students -- Attitudes.; Sociocultural theory -- Educational applications.